2006
DOI: 10.1124/jpet.106.102780
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Inotropic Effect of Nifekalant in Failing Hearts in Rats

Abstract: Class III antiarrhythmic agents have been widely used to suppress ventricular tachyarrhythmias in patients with heart failure because they have been shown to have positive inotropic effects as well. However, it remains to be examined whether those agents also exert positive inotropic effects in failing hearts. We addressed this important issue in a rat model of heart failure. We used Nifekalant as a representative class III antiarrhythmic agent. Four weeks after a s.c. injection of 60 mg/kg monocrotaline (MCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In addition, our previous report showed that MCT-rats exhibit a lower expression of SERCA2 protein and a relatively higher expression of NCX protein. 25 These properties of MCT-rats are consistent with past reports for the same experimental model 27,28 and for other animal models of ventricular hypertrophy. 29 Thus, we are convinced that MCT-rats can serve as a model of ventricular hypertrophy to examine the propagation features of Ca 2+ waves.…”
Section: Mct-induced Rv Hypertrophysupporting
confidence: 81%
See 3 more Smart Citations
“…In addition, our previous report showed that MCT-rats exhibit a lower expression of SERCA2 protein and a relatively higher expression of NCX protein. 25 These properties of MCT-rats are consistent with past reports for the same experimental model 27,28 and for other animal models of ventricular hypertrophy. 29 Thus, we are convinced that MCT-rats can serve as a model of ventricular hypertrophy to examine the propagation features of Ca 2+ waves.…”
Section: Mct-induced Rv Hypertrophysupporting
confidence: 81%
“…The steeper slope of the relationship in the MCT-rats may be due to the increased expression of the NCX. 19, 25 In conclusion, the results of the present study suggest that an increase in diastolic [Ca 2+ ]i and an increase in the Ca 2+ sensitivity of the SR Ca 2+ release channel accelerate Ca 2+ waves in ventricular hypertrophy, thereby causing arrhythmogenesis.…”
Section: Acceleration Of Ca 2+ Wavesmentioning
confidence: 84%
See 2 more Smart Citations
“…Heart failure can be identified by clinical symptoms that have been linked to hemodynamic indexes of right heart failure (15). Following MCT treatment, the RV action potential is prolonged (9,26,32). This is associated with decreased K ϩ channel activity, although studies disagree precisely which channels (26,27,32,41).…”
mentioning
confidence: 99%